Persistent Expression of Serotonin Receptor 5b Alters Breathing Behavior in Male MeCP2 Knockout Mice - Vogelgesang, Steffen; Niebert, Marcus; Bischoff, Anne M.; Hülsmann, Swen; Manzke, Till (Frontiers in Molecular Neuroscience, 2018)
Mutations in the transcription factor methyl-CpG-binding protein 2 (MeCP2) cause the neurodevelopmental disorder Rett syndrome (RTT). Besides many other neurological problems, RTT patients show irregular breathing with recurrent apneas or breath-holdings. MeCP2-deficient mice, which recapitulate this breathing phenotype, show a dysregulated, persistent expression of G-protein-coupled serotonin receptor 5-ht5b (Htr5b) in the brainstem. To investigate whether the persistence of 5-ht5b expression is contributing to the respiratory phenotype, we crossbred MeCP2-deficient mice with 5-ht5b-deficient mice to generate double knockout mice (Mecp2−/y;Htr5b−/−). To compare respiration between wild type (WT), Mecp2−/y and Mecp2−/y;Htr5b−/− mice, we used unrestrained whole-body plethysmography. While the breathing of MeCP2-deficient male mice (Mecp2−/y) at postnatal day 40 is characterized by a slow breathing rate and the occurrence of prolonged respiratory pauses, we found that in MeCP2-deficient mice, which also lacked the 5-ht5b receptor, the breathing rate and the number of pauses were indistinguishable from WT mice. To test for a potential mechanism, we also analyzed if the known coupling of 5-ht5b receptors to Gi proteins is altering second messenger signaling. Tissue cAMP levels in the medulla of Mecp2−/y mice were decreased as compared to WT mice. In contrast, cAMP levels in Mecp2−/y;Htr5b−/− mice were indistinguishable from WT mice. Taken together, our data points towards a role of 5-ht5b receptors within the complex breathing phenotype of MeCP2-deficient mice.